PENDAMPINGAN PROGRAM BTQ SISWA-SISWI MDTA HIDAYATUSSIBYAN - Dede Supendi (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2023)
This devotion-based research raises the issue of “BTQ Assistance Program for MDTA Hidayatussibyan Students in Cisalada Village, Kec. Jatiluhur Regency Purwakarta. One of the problems experienced by MDTA Hidayatussibyan students is the lack of effectiveness in learning the Koran. Learning to read and write the Koran should indeed be taught to Muslim students. One of the programs that will be carried out at KPM this time is the BTQ program for MDTA Hidayatussibyan students. The purpose of this community service activity with the assistance of the BTQ program is to improve the ability to read and write the Koran for MDTA Hidayatussibyan students. According to the research results, when conducting this KPM it shows that the BTQ program is carried out in the form of learning tajwid rules, training on how to pronounce hijaiyyah letters and reading the Al-Quran directly to the teacher. The method used in assisting the BTQ program is carried out using lecture methods, exercises or also known as drills, given assignments and through the ummi method. To learn to write is still basic, namely by forming hijaiyyah letters, connecting letters with other letters. The results of the BTQ program dedication showed that the ability to read and write the Koran in MDTA Hidayatussibyan students increased. This shows that the mentoring has been carried out successfully.